Postnatal development of NT3 and TrkC in mouse ventral cochlear nucleus. - Feng, J; Bendiske, J; Morest, D K (Journal of Neuroscience Research, 2010)
In the developing nervous system, neurotrophin 3 (NT3) and brain-derived neurotrophic factor (BDNF) have been shown to interact with each other and with different parts of a neuron or glia and over considerable distances in time and space. The auditory system provides a useful model for analyzing these events, insofar as it is subdivided into well-defined groups of specific neuronal types that are readily related to each other at each stage of development. Previous work in our laboratory suggested that NT3 and its receptor TrkC in the mouse cochlear nucleus (CN) may be involved in directing neuronal migration and initial targeting of inputs from cochlear nerve axons in the embryo. NT3 is hard to detect soon after birth, but TrkC lingers longer. Here we found NT3 and TrkC around P8 and the peak around P30. Prominent in ventral CN, associated with globular bushy cells and stellate cells, they were localized to different subcellular sites. The TrkC immunostain was cytoplasmic, and that of NT3 was axonal and perisomatic. TrkC may be made by CN neurons, whereas NT3 has a cochlear origin. The temporal pattern of their development and the likelihood of activity-dependent release of NT3 from cochlear axons suggest that it may not be critical in early synaptogenesis; it may provide long-term trophic effects, including stabilization of synapses once established. Activity-related regulation could coordinate the supply of NT3 with inner ear activity. This may require interaction with other neurotrophins, such as BDNF.
9 citations (Crossref) [2023-10-31] Place: United States Feng, J. Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Cochlear Nucleus/me [Metabolism]; *Neurons/me [Metabolism]; *Neurotrophin 3/me [Metabolism]; *Receptor; trkC/me [Metabolism]; Age Factors; Animals; Cochlear Nucleus; Fluorescent Antibody Technique; Gene Expression Regulation; Developmental; Mice; Microscopy; Fluorescence; NT3; Neurons; Neurotrophin 3; Postnatal development; Receptor; trkC; TrkC; Ventral cochlear nucleus (VCN); animal cell; animal experiment; article; brain derived neurotrophic factor; cellular distribution; cochlear nerve; cochlear nucleus; controlled study; cytoplasm; dept.bio; embryo; female; immunohistochemistry; inner ear; male; mouse; nerve cell; nerve fiber; nerve root; neurotrophin 3; neurotrophin 3 receptor; nonhuman; postnatal development; priority journal; protein interaction; regulatory mechanism; stellate cell; synapse; synaptogenesis

Technological variation in the earliest Oldowan from Gona, Afar, Ethiopia - Stout, Dietrich; Semaw, Sileshi; Rogers, Michael J.; Cauche, Dominique (Journal of Human Evolution, 2010)
Inter-site technological variation in the archaeological record is one of the richest potential sources of information about Plio-Pleistocene hominid behavior and evolution. However, appropriate methods for describing and comparing Oldowan assemblages have yet to be agreed upon, and interpretation of the early record remains highly controversial. Particularly salient is disagreement over whether the Oldowan is a single technological phenomenon or is more accurately divided into multiple regional and/or chronological traditions, perhaps including a less developed Pre-Oldowan phase in the late Pliocene. Some of this disagreement reflects theoretical and methodological differences between research traditions and some is more directly evidential. Here we present a framework for describing and interpreting Oldowan variation and apply it to three Pliocene assemblages (EG-10, EG-12, and OGS-7) from Gona, all dated to c. 2.6 million years (Ma). Results indicate proficient knapping and a full range of Oldowan reduction strategies in these earliest known occurrences, consistent with the idea of an Oldowan “technological stasis” from 2.6–1.6Ma. Patterns of variation in raw material selection and predominant reduction strategy at each site clearly indicate the importance of cultural transmission in the Oldowan, but confounding ecological and economic variation continue to render interpretation in terms of multiple tool making traditions or species inappropriate. We propose that cultural transmission and ecological adaptation should be recognized as complementary, rather than mutually exclusive, mechanisms in future attempts to explain Oldowan technological variation.
157 citations (Crossref) [2023-10-31] tex.ids: ISI:000279276600002, Rogers2010, lens.org/048-194-199-785-52X tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Animals; Archaeology; Chaîne opératoire; Chi-Square Distribution; Cultural Evolution; Early Stone Age; Environment; Ethiopia; Fossils; Gona; Hominidae; Humans; Lithic technology; Paleolithic; Paleontology; Pliocene-Pleistocene boundary; Pre-Oldowan; Stone Age; Tool Use Behavior; animal; archaeological evidence; archeology; chi square distribution; cultural anthropology; cultural geography; dept.ant; dept.bio; environment; evolution; fossil; geochronology; hominid; human; paleontology; peer-reviewed; spatial variation; technological development; technology adoption; tool use

The ratio of gametophytes to tetrasporophytes of intertidal chondrus crispus (gigartinaceae) across a salinity gradient - Guidone, Michele; Grace, Sean (Rhodora, 2010)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-225-776-360-25X tex.type: [object Object]
Keywords: Chondrus; Chondrus crispus; Gigartinaceae; dept.bio

Reproductive behavior in horseshoe crabs: Does density matter? - Mattei, Jennifer; Beekey, Mark A; Rudman, Adam; Woronik, Alyssa (Current Zoology, 2010)
While the four species of horseshoe crabs share many common reproductive traits with respect to their reproductive systems, they do differ with respect to their mating behavior (monogamy vs. polygynandry). Past research has attributed these differences to a number of factors including: spawning densities, operational sex ratios (OSR's), male condition (or age), environmental and/or genetic factors, or a combination thereof. Mating behaviors in the three Asian horseshoe crab species (Tachypleus gigas, T. tridentatus, and Carcinoscorpius rotundicauda) with low spawning densities and 1:1 operational sex ratios are typically monogamous. In Limulus polyphemus, mating behavior is more variable ranging from monogamy to polygynandry. Here we provide evidence, through a long term behavioral study, that variation in mating behavior is influenced by population density in L. polyphemus. Our study population on two beaches in Connecticut (Long Island Sound) have a spawning density 400 times less than that found in Delaware Bay (0.002 females/m2 vs. 0.8 females/m2) but similar operational sex ratios. Between 90%-95% of all spawning females in CT were paired with only one male, thus exhibiting monogamous behavior. In contrast, between 30 and 60% of spawning females in Delaware Bay have more than one mate and produce clutches of eggs with multiple paternities. Male condition played no role in mating behavior in CT populations. We also observed that on average 18% of the females on the spawning beaches are single. These results suggest that population density is an important condition that determines mating behavior. Also, low population density may lead to decreased mate finding ability and lost opportunities for spawning [Current Zoology 56 (5): 634-642, 2010]. © 2010 Current Zoology.
32 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-298-586-515-449 tex.type: [object Object]
Keywords: Carcinoscorpius rotundicauda; Limulus; Limulus polyphemus; Mating behavior; Merostomata; Monogamy; Polygynandry; Population density; Tachypleus gigas; dept.bio

Biotechnological potential of aquatic plant-microbe interactions. - Stout, L; Nusslein, K (Current opinion in biotechnology, 2010)
The rhizosphere in terrestrial systems is the region of soil surrounding plant roots where there is increased microbial activity; in aquatic plants, this definition may be less clear because of diffusion of nutrients in water, but there is still a zone of influence by plant roots in this environment [1]. Within that zone chemical conditions differ from those of the surrounding environment as a consequence of a range of processes that were induced either directly by the activity of plant roots or by the activity of rhizosphere microflora. Recently, there are a number of new studies related to rhizospheres of aquatic plants and specifically their increased potential for remediation of contaminants, especially remediation of metals through aquatic plant-microbial interaction. Copyright 2010 Elsevier Ltd. All rights reserved.
44 citations (Crossref) [2023-10-31] Place: England Stout, L. Department of Biology, Southern Connecticut State University, New Haven, CT 06515, United States. stoutl1@southernct.edu
Keywords: *Biotechnology/mt [Methods]; *Plants/mi [Microbiology]; 1 aminocyclopropanecarboxylic acid; Aquaculture; Aquatic plants; Biodegradation; Environmental; Biotechnology; Chemical conditions; Hydrogen-Ion Concentration; Microbial activities; Microbial interactions; Microflora; New study; Plant Roots; Plant Roots/mi [Microbiology]; Plant roots; Plants; Pollution; Rhizobium leguminosarum; Soils; Surrounding environment; Terrestrial systems; Zone of influences; adenosine triphosphatase; aquatic environment; aquatic flora; bacterial strain; biofilm; biofiltration; biotechnological procedures; biotechnology; cadmium; chromium; cobalt; copper; dept.bio; environmental exposure; heavy metal removal; homeostasis; metallothionein; microorganism; nickel; nonhuman; pH; phytochelatin; phytoremediation; plant growth; plant microorganism interaction; priority journal; process technology; protein binding; protein synthesis; review; rhizofiltration; rhizosphere; siderophore; transgene; volatilization; zinc